Pengembangan Aplikasi Sportyway: Aplikasi Pencari Teman Untuk Berolahraga Bersama Berbasis Lokasi - Muhammad Ananta Pratama; Agi Putra Kharisma; Adam Hendra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Sports is one of the most important activites in human life. Sports can help maintain our health and fitness so that we can always be ready to do our everyday things. Unfortunately, in this modern era many people fail to keep their sports routines with various reasons. One of the reasons is the lack of friend to do sports with which lowers our motivation to do sport. By using smartphone technology, this research offers a solution with an application named â€œSportywayâ€ which is a location-based friend finder application for spors activities. Besides increasing sport participation level in Indonesia's citizen, this application can help find new friends and help people to do sports regularly. In the development, this research uses Scrum method as its software development lifecycle. There are four processes in this research which is requirements analysis, design, implementation, and system testing. Requirements analysis produces ten functional requirements and two non-functional requirements. Obtained requirements then used as a guide to design the class diagram, activity diagram, database design, and algorithm design. From the design, program code implemented in Typescript programming language and using React Native framework. After implemented, system testing is the conducted using validation testing to make suree all features work well and usability testing to measure user satisfaction and ease in using developed application.